Effect of Dextran on Factor Vlll/von Willebrand Factor Structure and Function - Batlle, J; del Río, F; López Fernández, M F; Martín, R; López Borrasca, A (Thrombosis and Haemostasis, 1985)
Factor VIII/von Willebrand factor was analyzed before and after the infusion of 500 ml of Dextran 70 to normal volunteers. Factor VIII procoagulant activity, factor VIII related antigen and ristocetin cofactor activity showed a significant decrease, reaching after six hours the minimum level, which did not correlate with the hemodilution effect caused by dextran. Ristocetin-induced platelet agglutination (RIPA) in volunteers’ platelet-rich plasma (PRP) did not show any significant change between preinfusion time and six hours after the infusion. Multimeric analysis of von Willebrand factor (vWF) showed a progressive decrease of all the multimers which was more pronounced in the largest multimers. No change was seen in the “triplet” structure of vWF. No effect was noticed when dextran was incubated “in vitro” either with PRP or platelet-poor plasma. The modification induced by dextran is close to the pattern seen in subtype Ib von Willebrand’s disease.
Keywords: Dextran; Factor VIII/vWF; vWF multimeric structure